SERI PELATIHAN PEMBUATAN POT RAMAH LINGKUNGAN: UPAYA PEMBERDAYAAN PETANI ANGGREK DI PAPUA DAN PAPUA BARAT - Agustina Y.S. Arobaya; Ervizal A.M. Zuhud; Iskandar Z. Siregar; Irawati Irawati (JURNAL PENGABDIAN PAPUA, 2022)
Papuan orchid species have triggered orchid enthusiasts to be hunted for many purposes such as ornamental plants, medicinal plants and even to breeding program. This intention has encouraged locals who have the resources to trade orchids and extracted from their natural habitat without taking into consideration on how to sustain this resources for the future. Efforts should be conducted in order to enlighten the community not only to preserve this resources but also to encourage locals on how to gain benefit economically using orchids as income generate to support their daily life. Adding to this attempts, extension program such as using materials to create media to grow orchids from coconut waste and sago disposal as basic materials. We employed extension program, focus group discussion, short training course and practicum during the implementation of the activities in each location. Six sites were chosen where the orchid growers and nurseries run by locals and communities living in reserve and non-reserve areas. Five sites located in Jayapura Regency, Jayapura City, Keerom Regency, Biak Regency of Papua Province and Manokwari Regency at West Papua Province. Materials to create media to grow orchids comes from coconut waste and sago disposal as basic materials. Wires and metal screen were used to make frame for potting. We also use tools such as clipper to cut wire. All participants were actively showing their enthusiast to gain knowledge during the course. Some have ask about species name whereas others addressing question of how to reproduce the orchids as well as how to maintain the orchids using home made pot.Keywords:  Extension program; community empowerment; organic waste; orchids